Multi-year atmospheric concentrations of per- and polyfluoroalkyl substances (PFASs) at a background site in central Europe - Paragot, Nils; Bečanová, Jitka; Karásková, Pavlína; Prokeš, Roman; Klánová, Jana; Lammel, Gerhard; Degrendele, Céline (Environmental pollution (Barking, Essex, 2020)
A total of 74 high volume air samples were collected at a background site in Czech Republic from 2012 to 2014 in which the concentrations of 20 per- and polyfluoroalkyl substances (PFASs) were investigated. The total concentrations (gas + particle phase) ranged from 0.03 to 2.08 pg m-3 (average 0.52 pg m-3) for the sum of perfluoroalkyl carboxylic acids (∑PFCAs), from 0.02 to 0.85 pg m-3 (average 0.28 pg m-3) for the sum of perfluoroalkyl sulfonates (ΣPFSAs) and from below detection to 0.18 pg m-3 (average 0.05 pg m-3) for the sum of perfluorooctane sulfonamides and sulfonamidoethanols (ΣFOSA/Es). The gas phase concentrations of most PFASs were not controlled by temperature dependent sources but rather by long-range atmospheric transport. Air mass backward trajectory analysis showed that the highest concentrations of PFASs were mainly originating from continental areas. The average particle fractions (θ) of ΣPFCAs (θ = 0.74 ± 0.26) and ΣPFSAs (θ = 0.78 ± 0.22) were higher compared to ΣFOSA/Es (θ = 0.31 ± 0.35). However, they may be subject to sampling artefacts. This is the first study ever reporting PFASs concentrations in air samples collected over consecutive years. Significant decreases in 2012-2014 for PFOA, MeFOSE, EtFOSE and ∑PFCAs were observed with apparent half-lives of 1.01, 0.86, 0.92 and 1.94 years, respectively.
Keywords: Carboxylic Acids; Environmental Monitoring; Seasonal variations; Multi-year variations; monitorování životního prostředí; Long-range atmospheric transport; Gas-particle partitioning; fluorokarbony; Česká republika; kyseliny karboxylové; Fluorocarbons; Europe; Evropa; Czech Republic; Per- and polyfluoroalkyl substances